The Impact of Educators' Teaching Styles on Secondary School Learners' Motivation in English - Wiangga, Ilhan Arya; febriyanto, Nurhaifuddin Ivan (Yayasan Lembaga Studi Makwa, 2024)
The purpose of this study is to explore how student learning motivation in English courses relates to the teaching style of the teacher. Twenty learners in the XII grade at Mamba'us Sholihin High School in Blitar during the 2024–2025 school year serve as the research topic for this kind of quantitative investigation. The study's variables were the independent variable of instructor teaching style and the dependent variable of student learning motivation. Student learning motivation and teacher teaching style questionnaires were the tools utilized. Questionnaires and documentation were used as data collecting methods. Descriptive analysis in the form of percentages and correlation analysis using chi square were employed in the data analysis. According to the findings of the descriptive analysis, 30% of students believed that the teacher had a good teaching style, while the remaining 70% said that the teacher did not. According to the findings of a descriptive study on student learning motivation, just 30% of students have a high interest in learning, while 70% of students have a poor interest. In class XII SMA Mamba'us Sholihin Blitar, the results of the chi square analysis showed a substantial correlation between the teacher's teaching style and the students' enthusiasm to learn (CC = 0.606, P = 0.002). It is clear from the goals and data analysis that the instructor's method of instruction has a strong effect on student learning motivation.